2020
DOI: 10.1055/s-0040-1718431
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal-Facial Anastomosis for Facial Nerve Reconstruction: Outcomes using the Side-to-End Surgical Technique

Abstract: Introduction The side-to-end hypoglossal-facial anastomosis (HFA) technique is an excellent alternative technique to the classic end-terminal anastomosis, because it may decrease the symptoms resulting from hypoglossal-nerve transection. Methods Patients with facial nerve palsy (House-Brackmann [HB] grade VI) requiring facial reconstruction from 2014 to 2017were retrospectively included in the study. Results In total, 12 cases were identified, with a mean follow-up of 3 years. The causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A retroauricular-arch incision was made, exposing the mastoid process and extending caudally along the anterior border of the sternocleidomastoid muscle until just above the angle of the mandible ( Figure 1A ) ( 12 ). Attention was given to avoid injury to the greater auricular nerve ( Figure 1B ).…”
Section: Surgical Techniques and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A retroauricular-arch incision was made, exposing the mastoid process and extending caudally along the anterior border of the sternocleidomastoid muscle until just above the angle of the mandible ( Figure 1A ) ( 12 ). Attention was given to avoid injury to the greater auricular nerve ( Figure 1B ).…”
Section: Surgical Techniques and Resultsmentioning
confidence: 99%
“…In microscopic surgery, the styloid process ( Figures 2B,C ) is traditionally used as a landmark for localizing the stylomastoid foramen and the main trunk of the facial nerve ( 12 , 13 ). Using an endoscope, we found that the facial nerve and its branches were located more superficially than the styloid process ( Figures 2B,C ), and we could easily identify them without using the styloid process as a landmark, both in the stylomastoid foramen area ( Figure 2C ) and within the parotid gland ( Figure 2E ).…”
Section: Surgical Techniques and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruschel et al (2020) analyzed the 'side-to-end' HFA technique to assess seven patients with FP secondary to VS resection [ 7 ]. All patients initiated with grade VI on the HB scale, and all exhibited positive outcomes.…”
Section: Reviewmentioning
confidence: 99%